Converting existing buildings to green buildings: implementations in Turkey - Aktaş, Bahacan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Environmental challenges like global warming, climate change and fresh water supply has recently become an important issue. However, humankind continues to harm the nature and waste natural resources. Large amounts of energy consumption and water use all over the world result from buildings and also a large part of human life time is spent in buildings. All these reasons bring green buildings into the front scene that are environmental friendly, sustainable, more comfortable, energy efficient and low consuming structures. Developed countries have a comprehensive knowledge of green building and sustainability concepts and have been working with this awareness for more than 20 years. They established different environmental performance assessment systems. However, there has been lack of awareness in developing countries like Turkey. Since there are thousands of old and inefficient buildings in Turkey’s building stock and still a large housing deficit, green building concept is a great opportunity for the country. Since green building is a relatively new concept in Turkey, there are certain questions both in owners’ and end users’ minds about green building implementations, supplying environmental friendly construction materials, encountering additional costs in a green building project etc. There are many studies about green new construction projects; however there is less information about greening existing buildings. This research is based on investigation of factors influencing green retrofit and renovation projects and the ways in which such projects can be completed efficiently and effectively in Turkey.
Keywords: Leadership in Energy and Environmental Design Green Building Rating System.; Green products -- Turkey.